Fear Of Failure Dan Student Engagement Pada Mahasiswa Tahun Pertama Fakultas Psikologi Universitas Negeri Makassar: Nabilah Hafizhah Ahmad, Ahkam Alwi, Nur Akmal - Hafizhah Ahmad, Nabilah; Alwi, Ahkam; Akmal , Nur (Fakultas Psikologi Universitas Bhayangkara Jakarta Raya, 2024)
Students have a role to be involved in the learning process. Student engagement in the success of learning is essential. Based on the survey results, student engagement is not fulfilled in first-year students of the psychology faculty at Makassar State University. This is due to several factors, including not playing an active role in class; this is due to the emergence of fear of lousy assessment, a negative individual interpretation of this condition and can also be called fear of failure. This research aims to see if there is a relationship between fear of failure and student engagement in first-year students studying at the psychology faculty of Makassar State University. In this study, the researchers used a purposive sampling technique with a total sample of 227 first-year psychology students at Makassar State University, p=0.00 (p<0.05) between student engagement and fear of failure. Ho is rejected, and Ha is accepted. The results of the influence of fear of failure of 8.3% and the remaining 91.7% were contributed by other variables that researchers did not use. This research is expected to provide an overview to first-year students regarding fear of failure and student engagement.